1997
DOI: 10.1093/emboj/16.12.3426
|View full text |Cite
|
Sign up to set email alerts
|

Aerolysin and pertussis toxin share a common receptor-binding domain

Abstract: We have discovered that the bacterial toxins aerolysin and pertussis toxin share a common domain. This is surprising because the two toxins affect cells in very different ways. The common domain, which we call the APT domain, consists of two three‐stranded antiparallel β‐sheets that come together and wrap around a central pair of helices. The APT domain shares a common fold with the C‐type lectins and Link modules, and there appears to be a divergent relationship among the three families. One surface region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 48 publications
6
49
0
Order By: Relevance
“…1C, 3, and 5). In addition, the region in which sequence similarity is observed is restricted to the pore-forming domain, suggesting that the receptor binding domain is a functionally and structurally autonomic module as suggested previously (48,56). This would explain the similarity in the binding of all Hln isoforms (including the inactive isoform rHln-3) to erythrocyte membranes, as most of the differences between these isoforms are found in the suggested pore-forming region, whereas the rest of the proteins (presumably including the receptor binding domain) are similar.…”
Section: Discussionsupporting
confidence: 57%
“…1C, 3, and 5). In addition, the region in which sequence similarity is observed is restricted to the pore-forming domain, suggesting that the receptor binding domain is a functionally and structurally autonomic module as suggested previously (48,56). This would explain the similarity in the binding of all Hln isoforms (including the inactive isoform rHln-3) to erythrocyte membranes, as most of the differences between these isoforms are found in the suggested pore-forming region, whereas the rest of the proteins (presumably including the receptor binding domain) are similar.…”
Section: Discussionsupporting
confidence: 57%
“…For one of these domains, the receptor-binding domain, previous work carried out on aerolysin (10,(13)(14)(15) as well as experiments conducted in this study provided evidence to its probable location in D1. Based on this knowledge, scanning was initiated in this region and alanine was chosen for substitution due to its minimal side chain.…”
Section: Mutagenesis Strategysupporting
confidence: 62%
“…Rossjohn et al have shown that D1 of aerolysin contains a motif similar to the carbohydrate-binding domain of pertussis toxin, now named the aerolysin pertussis toxin domain (15). Fusion of this domain to the amino terminus of AT converts it to an aerolysinlike toxin such that it can bind to receptors previously only bound by aerolysin.…”
mentioning
confidence: 99%
“…The greater binding could well be due to the higher abundance of N-linked sugars or other oligosaccharides on the apical surface. As recently shown by Hong et al (24), high-affinity binding of aerolysin to its receptor requires not only the glycan core of the GPI-anchored protein but also the interaction of the lectin-like domain 1 of aerolysin (36) with an N-linked sugar on the receptor. Interestingly, it appears that this N-linked sugar must be in close proximity to the GPI anchor, possibly forming a combined binding site, since domain 1 will bind with high affinity only to N-glycans on GPI-anchored proteins.…”
Section: Discussionmentioning
confidence: 90%